Kontroversi Kesejarahan Pengarang Bahrul Lahut Antara Ulama Aceh dan Ulama Minangkabau - Mashuri (MAARIF, 2023)
Studies on the history of the author of Bahrul Lahut, namely Sheikh Abdullah Arif, have never been carried out, even though there are different versions, especially between sources in Aceh and sources in Minangkabau. Therefore, this research seeks to uncover the controversy over Bahrul Lahut’s authorship and touch on its content as a preliminary study because the two are interconnected. This research uses a philological, archaeo-genealogical and historical approach. The aim of the research is to reveal the content of Bahrul Lahut and the history of its author which is still related to the teachings in the manuscript. The results of the study, (1) Bahrul Lahut’s content describes the creation of the universe which is influenced by Ibn Arabi’s understanding of wahdatul form and emanation. (2) The genealogy of Bahrul Lahut’s knowledge has the same paradigm as the spirit of the revision of the wujudiyah ideology carried out by Sheikh Abdurrouf Singkel, who attempted to reconcile the conflict between the wujudiyah and syuhudiyah ideologies in Islamic circles in the archipelago. (3) Sheikh Abdullah Arif is not a single figure because in several sources it is stated that he is not only considered a scholar from the 12th century during the Samudera Pasai Kingdom, but is also known as the first teacher of Sheikh Burhanuddin Ulakan, who was a student of Sheikh Abdurrouf Singkel. Referring to the genealogy of knowledge of works and sources from Minangkabau, the history of Sheikh Abdullah Arif is closer to the time of Sheikh Abdurrouf Singkel, namely the period of the Aceh Darussalam Kingdom (17th century), so previous claims state that he lived during the Samudera Pasai Kingdom (17th century - 12) deserves to be questioned again.